Bone Resection for Isolated Ulnar Head Fracture - Hiromasa Akino; Shunpei Hama; Masataka Yasuda; Kenta Minato; Masahiro Miyashita (Case Reports in Orthopedics)
Distal ulnar fractures often occur with distal radius fractures (DRFs), and ulnar styloid fractures commonly occur in the setting of DRF. However, isolated ulnar head fractures are rare. We report a case of isolated ulnar head fracture in which we performed bone resection because the ulnar head bone fragment fractured when internal screw fixation was attempted. His outcome at 18 months postoperatively was considered excellent. However, we do not advocate bone resection other than failure of fixation and the difficult case to perform internal fixation. Longer follow-up would be needed because bone resection might lead to osteoarthritis of the distal radioulnar joint in the future.